Indonesia’s Obligation to Protect Archaeological and Historical Objects at Sea based on UNCLOS 1982 - Latuputty, Marcelino H. (Indonesian Journal of International Law, 2019)
The protection of archaeological and historical objects found at sea, one of them was contained in 1982 UNCLOS. Indonesia as the State Party of UNCLOS has the obligation to protect such objects. However, provisions regarding the protection of such objects in UNCLOS was considered as obscure and ambiguity. Otherwise, the protection of such objects furthermore arranged in 2001 UNESCO Convention on Underwater Cultural Heritage. Unfortunately, Indonesia is not the party of the 2001 UNESCO Convention. This fact makes Indonesia’s obligation in international law is confined only on UNCLOS. Therefore, the aim of this article is to explain regarding Indonesia’s Obligation to Protect Archaeological and Historical Objects Found at Sea Based on the 1982 UNCLOS, and also the regulations and the practices of Indonesia’s national law. In the Indonesian legal system, there are several national regulation which cover the protection and preservation of UCH. However, the matter related to the disharmony of laws and regulations for the protection and preservation of UCH, nor the lack of implement regulation, leading the protection and preservation of UCH to less optimal. In this context, Government needs to emphasize that the protection is pure for the purpose of conservation only, or can it be utilized and manageable for commercial purpose in certain condition. Therefore, will create legal certainty concerning the protection and preservation of UCH.